Linking Women with Agribusiness in Zambia : Corporate Social Responsibility, Creating Shared Value, and Human Rights Approaches - White, Pamela; Finnegan, Gerry; Pehu, Eija; Poutiainen, Pirkko; Vyzaki, Marialena (World Bank, Washington, DC, 2015)
Three of sub-Saharan Africa’s central economic realities motivate this study. First, agriculture is the most important sector in most African economies, on average accounting for nearly one-fourth of GDP. Second, the private sector is increasingly active in transforming African agriculture and economies. By 2030, agriculture and agribusiness are anticipated to become a US$ 1 trillion industry in Africa, delivering more jobs, income, and economic growth. Third, women make up half of sub- Saharan Africa’s agricultural labor force on average (and two-thirds or more in some countries). Yet women’s strong presence in agriculture belies the comparatively weak commercial benefits they derive from it. Throughout Africa, women struggle to enter and operate highly productive and profitable agricultural enterprises. Their plots of land tend to be smaller, their crops less remunerative, and their access to land, inputs, and finance far more restricted and precarious than men’s. Africa boasts the highest share of ‘entrepreneurs,’ but these women are disproportionately concentrated in the ranks of the self-employed rather than among the employers. Women’s productivity is lower than men’s, not because they are women, but because informal, smaller firms are inherently less productive, and more women operate these types of enterprises. The real challenge in expanding opportunities and empowering women is not to help more women to become small-scale, informal entrepreneurs but to enable them to shift to activities capable of delivering higher returns and employing others.